Metabolic changes after nonsurgical fat removal: A dose response meta-analysis. (February 2023) - Badran, Saif; Doi, Suhail A.; Iskeirjeh, Sara; Aljassem, Ghanem; Jafarian, Nasrin; Clark, Justin; Habib, Abdella M.; Glass, Graeme E.
Summary: Background: Obesity-induced insulin resistance leads to the metabolic syndrome. Both bariatric surgery and surgical fat removal have been shown to improve metabolic health, but the metabolic benefits of nonsurgical fat removal remain uncertain. The aim of this paper is to establish whether nonsurgical fat removal exerts measurable, lasting metabolic benefits by way of changes to serum lipid profiles. Methods: PubMed, Cochrane CENTRAL, Embase, and clinical trials registers were searched using the Polyglot Search Translator to find studies examining quantitative changes in metabolic markers after nonsurgical body contouring procedures. The MethodologicAl STandard for Epidemiological Research (MASTER) scale was adopted for the quality assessment of the included studies. The robust-error meta-regression (REMR) model was employed. Results: Twenty-two studies and 676 participants were included. Peak body compositions measures manifest as a reduction of 2 units in body mass index (BMI), 1 kg of body weight (BW), 5 cm in waist circumference (WC) and 1.5 cm in abdominal fat thickness (FT), sustained up to 60 days postprocedure. Transient increases of 15 mg/dL in low-density lipoprotein (LDL), 10 mg/dl in triglycerides (TG), and 15 mg/dl in total cholesterol (TC) were observed at 2 weeks postprocedure. Conclusion: While nonsurgical fat removal exerts sustained effects on body anthropometrics, changes to serum lipid profiles were transient. There is no compelling evidence at present to support the conclusion that nonsurgical fat removal is metabolically beneficial.